DAMPAK PENAMBANGAN PASIR TERHADAP KONDISI LAHAN DAN AIR DI KECAMATAN SUKARATU KABUPATEN TASIKMALAYA - Dini Widyasmarani Suherman; Dyah Tjahyandari Suryaningtyas; Sri Mulatsih (Graduate School Bogor Agricultural University (SPs IPB), 2015)
Sand is an important commodity for constructions. The largest sand mining in Tasikmalaya District is located in Sukaratu Sub District. This mining activites have a negative impact for the environment such as causing erosion and water pollution. This study was aimed to assess the impact of sand mining on the land and water conditions. The analysis method that was used in this study is the analysis of erotion rate using Universal Soil Loss Equation (USLE) formula and the analysis of Total Suspended Solid (TSS) parameters. The results showed that the rate of erosion ranged from 163.49 to 1,194.16 ton/ha/year, with erosion hazard rate (TBE) were very heavy. The TSS value of Cibanjaran and Cikunir river water ranged from 26 to 186 mg/liter, this values were below the threshold but the effect is not good for the fishery.Keywords: erosion rate, sand mining, Total Suspended Solid (TSS) doi: 10.19081/jpsl.5.2.99